2023
DOI: 10.3390/metabo13010079
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Predictors of Coronary No-Reflow

Abstract: The ‘no-reflow’ phenomenon (NRP) after primary percutaneous coronary intervention (PCI) is a serious complication among acute ST-segment elevation myocardial infarction (STEMI) patients. Herein, a comprehensive lipidomics approach was used to quantify over 300 distinct molecular species in circulating plasma from 126 patients with STEMI before and after primary PCI. Our analysis showed that three lipid classes: phosphatidylcholine (PC), alkylphosphatidylcholine (PC(O)), and sphingomyelin (SM), were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Non reflow after percutaneous coronary intervention (PCI) refers to the failure of coronary artery blood flow to return to normal after PCI, resulting in the myocardium remaining in an ischemic state. This may be due to the incomplete dissolution or re formation of blood clots [ 242 ]. TXL is one of the preventive strategies for cardiovascular events after PCI and is widely used in China, but its effectiveness and safety have not been systematically evaluated.…”
Section: Clinical Research On the Prevention And Treatment Of Cardiov...mentioning
confidence: 99%
“…Non reflow after percutaneous coronary intervention (PCI) refers to the failure of coronary artery blood flow to return to normal after PCI, resulting in the myocardium remaining in an ischemic state. This may be due to the incomplete dissolution or re formation of blood clots [ 242 ]. TXL is one of the preventive strategies for cardiovascular events after PCI and is widely used in China, but its effectiveness and safety have not been systematically evaluated.…”
Section: Clinical Research On the Prevention And Treatment Of Cardiov...mentioning
confidence: 99%
“…Another CMR imaging study showed modest association (adjusted odds ratio of 1.02) between elevated low-density lipoprotein (LDL) cholesterol level and microvascular injury in 235 patients with STEMI undergoing primary PCI [251]. A recent lipidomics study showed that phosphatidylcholine, alkylphosphatidylcholine, and sphingomyelin, were significantly elevated in plasma of patients with STEMI who developed CNR after primary PCI [252]. Despite well-known deleterious effects of smoking on vasculature, including endothelial dysfunction, vascular remodeling, increased thrombogenicity and proinflammatory action [253], recent CMR imaging studies in reperfused patients with STEMI did not show a significant difference in the presence or extent of MVO in smokers vs. nonsmokers [254][255][256].…”
Section: Individual Susceptibility To Cnrmentioning
confidence: 99%